2012
DOI: 10.1093/cercor/bhs186
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Modular Organization of Functional Networks in Cognitively Impaired Children with Frontal Lobe Epilepsy

Abstract: Many children with frontal lobe epilepsy (FLE) have significant cognitive comorbidity, for which the underlying mechanism has not yet been unraveled, but is likely related to disturbed cerebral network integrity. Using resting-state fMRI, we investigated whether cerebral network characteristics are associated with epilepsy and cognitive comorbidity. We included 37 children with FLE and 41 healthy age-matched controls. Cognitive performance was determined by means of a computerized visual searching task. A conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 58 publications
5
72
0
5
Order By: Relevance
“…There was a weak association between connectivity in the right superior frontal gyrus of the frontal network and executive function and a significant association between connectivity in the right paracentral lobule of sensorimotor network and fine motor function. Vaessen et al 18 also found that higher modularity scores on resting-state fMRI were associated with decreased cognitive performance, as measured by increased computerized visual searching task reaction time. These findings suggest that impaired functional networks may be part of the neural underpinning for neuropsychological impairment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There was a weak association between connectivity in the right superior frontal gyrus of the frontal network and executive function and a significant association between connectivity in the right paracentral lobule of sensorimotor network and fine motor function. Vaessen et al 18 also found that higher modularity scores on resting-state fMRI were associated with decreased cognitive performance, as measured by increased computerized visual searching task reaction time. These findings suggest that impaired functional networks may be part of the neural underpinning for neuropsychological impairment.…”
Section: Discussionmentioning
confidence: 97%
“…The greater number of pair-wise ICs for the DMNattention and DMN-auditory networks in our study could be for the same reason. Vaessen et al 18 evaluated the resting-state connectivity by use of graph theoretical metrics of whole-brain networks. They found that children with FLE have a decrease in longrange and an increase in interhemispheric connectivity, as well as higher modularity scores, suggesting the presence of more functionally isolated brain modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that behavioral deficits in epilepsy may be the result of disrupted activity within associated resting-state networks, due to repeated seizure activity. A previous fMRI study reported that children with FLE had an increased number of functional connections within the frontal lobe, but a decreased number of functional connections between the frontal lobe and the rest of the brain (Vaessen et al, 2012). Furthermore, the extent of this frontal lobe isolation was positively correlated with the degree of cognitive impairment.…”
Section: Introductionmentioning
confidence: 90%
“…If the way the two regions vary is related, then they are said to be correlated. Correlati using fMRI data are plentiful and have looked at many things from the modular organization of functional networks in children with frontal lobe epilepsy (Vaessen et al, 2012), to language networks in subjects with anophthalmia (Watkins et al, 2012), to the reliability of the identification of the default mode network (Long et al, 2008). Partial correlation is also a widely used method which seeks to identify direct connections, rather than the direct and the indirect as identified with correlation , by regressing out information from all additional regions in the network in considering the relationship between two regions.…”
Section: Correlation Based Modelsmentioning
confidence: 99%